2017
DOI: 10.1007/s00404-017-4443-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC2 rs13181 polymorphism and ovarian cancer risk: an updated meta-analysis with 4024 subjects

Abstract: The present study suggests that the ERCC2 gene rs13181 polymorphism might be associated with increased risk of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To date, only a limited number of studies have identified SNPs in DNA damage repair genes, delineating their implications in the risk [ 4 ], prognosis [ 5 ]and chemotherapy response [ 6 ] of ovarian cancer. Hence, the biological significance of SNPs of other genes in DDR pathway needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a limited number of studies have identified SNPs in DNA damage repair genes, delineating their implications in the risk [ 4 ], prognosis [ 5 ]and chemotherapy response [ 6 ] of ovarian cancer. Hence, the biological significance of SNPs of other genes in DDR pathway needs to be explored.…”
Section: Introductionmentioning
confidence: 99%